Weak Soft (1,2)*- -Sets and Weak Soft (1,2)*- -Separation Axioms in Soft Bitopological Spaces - Mahmood, Sabiha I; Abdul-Hady, Asaad Adel (Al-Nahrain Journal of Science, 2019)
In this article we introduce and characterize new types of soft sets in soft bitopological spaces, namely, soft (1,2)*-omega difference sets (briefly soft (1,2)*- -sets) and weak forms of soft (1,2)*-omega difference sets. Moreover we use these soft sets to study new types of soft separation axioms, namely, soft (1,2)*-ω- -spaces, soft (1,2)*-α-ω- -spaces, soft (1,2)*-pre-ω- -spaces, soft (1,2)*-b-ω- -spaces and soft (1,2)*-β-ω- -spaces, for . Furthermore we investigate the characterizations and the relations between these types of soft separation axioms and other soft separation axioms.